2020
DOI: 10.1155/2020/5036585
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory Muscle Training in Obstructive Sleep Apnea Associating Diabetic Peripheral Neuropathy: A Randomized Control Study

Abstract: Objective. This work is aimed at assessing the effects of inspiratory muscle training on lung functions, inspiratory muscle strength, and aerobic capacity in diabetic peripheral neuropathy (DPN) patients with obstructive sleep apnea (OSA). Methods. A randomized control study was performed on 55 patients diagnosed with DPN and OSA. They were assigned to the training group (IMT, n=28) and placebo training group (P-IMT, n=27). Inspiratory muscle strength, lung functions, and aerobic capacity were evaluated before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(49 citation statements)
references
References 54 publications
0
49
0
Order By: Relevance
“…[ 12 , 13 ] In addition, a recent study approved that IMT may enhance respiratory muscle strength and improves aerobic capacity among patients with respiratory muscle weakness. [ 14 ] In addition, previous systematic reviews documented that IMT may improve inspiratory muscle strength and endurance, and diminishes dyspnea. [ 15 17 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 , 13 ] In addition, a recent study approved that IMT may enhance respiratory muscle strength and improves aerobic capacity among patients with respiratory muscle weakness. [ 14 ] In addition, previous systematic reviews documented that IMT may improve inspiratory muscle strength and endurance, and diminishes dyspnea. [ 15 17 ]…”
Section: Introductionmentioning
confidence: 99%
“…Of these, 12 were excluded for conference abstract, two for wrong intervention, one for wrong population, and one for wrong publication type. Ultimately, eight studies met the criteria for eligibility and were included in the review [ 16 , 17 , 21 , 22 , 23 , 24 , 25 , 26 ]. The flow chart of the study selection process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were conducted in the USA [ 17 , 26 ], two in Taiwan [ 23 , 25 ], two in Brazil [ 16 , 21 ], one in Egypt [ 22 ], and one in Turkey [ 24 ]. All studies were published after 2016.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that CDH children who were more active preserved a higher level of performance with less perception of dyspnea and effort compared to children who were less active [ 34 ]. Also, Moawd et al concluded that inspiratory muscle training improves inspiratory muscle strength and aerobic capacity in patients experiencing obstructive sleep apnea [ 35 ].…”
Section: Discussionmentioning
confidence: 99%